Advertisement

So, for this sequence whose nth term is given by an = n, we
have  

the summation of k as k goes from 1 to 5 ... start at k = 1, which gives 1, then let k = 2, which gives + 2, then let k = 3, which gives + 3, then let k = 4, which gives + 4, Finally, let k = 5, which gives + 5. Done! ... add them up! = 15

Let's do another one so you can get more used to the notation.

Let's find the sum:

the summation of 2k as k goes from 3 to 6

Crunch it out!

the summation of 2k as k goes from 3 to 6 ... k = 3 gives 2 ( 3 ) , k = 4 gives 2 ( 4 ) , k = 5 gives 2 ( 5 ) , k = 6 gives 2 ( 6 ) ... add them up ... = 36

See?  Now, that wasn't that bad!